The role, mechanism, and application of RNA methyltransferase METTL14 in gastrointestinal cancer - Shi, Bin; Liu, Wei-Wei; Yang, Ke; Jiang, Guan-Min; Wang, Hao (Molecular cancer, 2022)
Gastrointestinal cancer is the most common human malignancy characterized by high lethality and poor prognosis. Emerging evidences indicate that N6-methyladenosine (m6A), the most abundant post-transcriptional modification in eukaryotes, exerts important roles in regulating mRNA metabolism including stability, decay, splicing, transport, and translation. As the key component of the m6A methyltransferase complex, methyltransferase-like 14 (METTL14) catalyzes m6A methylation on mRNA or non-coding RNA to regulate gene expression and cell phenotypes. Dysregulation of METTL14 was deemed to be involved in various aspects of gastrointestinal cancer, such as tumorigenesis, progression, chemoresistance, and metastasis. Plenty of findings have opened up new avenues for exploring the therapeutic potential of gastrointestinal cancer targeting METTL14. In this review, we systematically summarize the recent advances regarding the biological functions of METTL14 in gastrointestinal cancer, discuss its potential clinical applications and propose the research forecast.